PERAN KEADILAN PROSEDURAL DAN KEADILAN ANTAR PRIBADI DALAM MENENTUKAN KEBERHASILAN DAN KEPUASAN PENANGANAN KOMPLAIN - Angga Pandu Wijaya; Widya Prananta; Made Virma Permana (Jurnal Bisnis Terapan, 2023)
Service companies often face complaints due to the challenges of providing standardized services. Unlike manufacturers that produce standardized products using machines, service companies are more susceptible to consumer complaints. Procedural justice and interpersonal justice are factors that determine the success rate of complaint handling. This study aims to examine the impact of procedural justice and interpersonal justice on complaint satisfaction through complaint handling. The study adopted a quantitative approach and involved a sample of 181 respondents, specifically consumers who have filed complaints with service companies. The test results demonstrate that both procedural justice and interpersonal justice significantly influence the effectiveness of complaint handling. The research also confirms that complaint satisfaction is influenced by both procedural justice and interpersonal justice. The study's findings indicate that successful complaint handling partially mediates the relationship between procedural justice, interpersonal justice, and complaint satisfaction. This research underscores the importance of procedural justice and interpersonal justice for service companies. They should prioritize complaint handling to establish customer loyalty and prevent negative word-of-mouth.